Rural Farms as a Strategy for the Development of Agritourism: A Study in the City of Milagro, Ecuador - SALTOS-LAYANA, Andrea; CARVACHE-FRANCO, Mauricio; CASTRO-ITURRALDE, Galo; CARVACHE-FRANCO, Wilmer; GRANDA-MALDONADO, Santiago; CARVACHE-FRANCO, Orly (Journal of Environmental Management and Tourism; Vol 14 No 3 (2023): JEMT, Volume XIV, Issue 3(67), Summer 2023, 2023)
This article aims to evaluate the current conditions of rural farms located in Milagro-Ecuador to analyze the importance of development of agritourism in this city. The study was carried out through the application of a questionnaire to know the perspectives of the owners of tourist farms. The findings showed that most of the tourist farms in the city are managed by the family, main activity of the farms is still agriculture, however they have decided to invest in tourism as an activity of additional economic income, that indicates that farm-based tourism in farming offers some potential to generate supplemental revenues. This study provides useful information for understand this kind of business and its implications in order to facilitate the integrated and Sustainable Tourism Planning of this city.